Availability of Facilities Supports Education Across All School Levels: Case Study of SDN 1 Sabaru - Ricko Jordan Manuputty; Penti Penti; Meti Agustina; Nanda Anjelia; Rinie Rinie (Journal of Instructional and Development Researches, 2023)
Completeness of educational facilities at SD Negeri 1 Sabaru, according to the author's observations, has not been fulfilled in supporting education at school even though it is said to be quite good, but there are still many complete facilities that must be addressed and completed in supporting the educational process at SD Negeri 1 Sabaru. The purpose of this research on infrastructure facilities at SD Negeri 1 Sabaru is to find out the infrastructure facilities in the SD Negeri 1 Sabaru environment, in management, procurement, maintenance by school residents to maintain the facilities provided by the school. Therefore, it is expected that the existence of complete educational facilities can increase the activity of student learning activities. Field research, the subject number consists of 3 people, the study population with the Principal, Teachers, and students of SD Negeri 1 Sabaru. Research, the authors sought data by collecting and processing the findings. Three informants, namely the principal, teachers, and sixth grade students of SD Negeri 1 Sabaru, collected information. Collected data are school facilities and infrastructure, facilities and infrastructure include facilities in the form of school buildings, classrooms for teaching and learning activities, sports venues, and skills venues, and others. Based on data collected, school facilities and infrastructure include facilities in the form of school buildings, classrooms for teaching and learning activities, sports venues, and skills venues, etc. This study concludes that school facilities must be adequate in terms of school facilities and infrastructure in order to achieve all aspects of education at SD Negeri 1 Sabaru, but still maximize existing facilities. The results concluded that facilities are essential for education in all school location contexts.